Disclosure of Sustainability Consciousness in Elementary School Students: Application of Education for Sustainable Development through the Introduction of Green Behavior - Yulianto, Ade; Widodo, Ari; Syaodih , Ernawulan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
After the â€œ2030 Agenda for Sustainable Developmentâ€ with 17 Sustainable Development Goals (SDGs) has become a global consensus in 2015, its implementation raises questions about the role of education in achieving these goals. Because education clearly covers the content of all the SDGs and provides the skills and competencies needed to face the challenges of a sustainable future. Education for sustainable development (ESD) is the role of education to promote sustainable development, which in this study is applied through the introduction and implementation of green behavior activities in elementary schools. The purpose of this study is to measure the sustainability consciousness of elementary school students through the implementation of ESD in elementary schools. This research is an experimental research in the form of pre-experimental design (single group designs). The instrument used in this research is the Sustainability Consciousness Questionnaire (SCQ) which allows the investigation of students' knowledge, attitudes, and behavior of sustainability. The results of this study indicate that students who have been given an education for sustainable development program through the introduction of green behavior experience a significant increase in sustainability consciousness. The implications of this research provide an overview of cognitive and affective responses to students regarding issues that are the scope of ESD such as global issues, issues related to human sustainability, consciousness of recovery from environmental damage that is happening today, and thinking about how to preservation is able to survive and can fulfill life in the future.